2010
DOI: 10.1016/j.neuroscience.2010.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroid regulation of the midbrain corticotropin releasing factor and urocortin systems in macaques

Abstract: A significant number of postmenopausal women report increased anxiety and vulnerablity to stress, which has been linked to decreased secretion of ovarian steroids. Communication between the serotonin system and the CRF system determines stress sensitivity or resilience. This study examines the effects of the ovarian steroids, estradiol (E) and progesterone (P) on the CRF system components that impact serotonin neurons in the midbrain of nonhuman primates. Ovariectomized rhesus macaques were treated with placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 86 publications
(107 reference statements)
3
29
0
1
Order By: Relevance
“…Thus, it has been generalized that activation of CRF-R1 by CRF increases anxiety-like behavior whereas activation of CRF-R2 by UCN1 decreases anxiety-like behavior. CRF-R1 and R2 receptors are present in the dorsal raphe of macaques (Sanchez et al, 2010). Therefore, we hypothesized that UCN1 fiber density would be lower in SS animals and that CIT would increase UCN1 fiber density.…”
Section: Ucn1 Fiber Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been generalized that activation of CRF-R1 by CRF increases anxiety-like behavior whereas activation of CRF-R2 by UCN1 decreases anxiety-like behavior. CRF-R1 and R2 receptors are present in the dorsal raphe of macaques (Sanchez et al, 2010). Therefore, we hypothesized that UCN1 fiber density would be lower in SS animals and that CIT would increase UCN1 fiber density.…”
Section: Ucn1 Fiber Densitymentioning
confidence: 99%
“…CRF receptors have been detected in the raphe of rodents (Chalmers et al, 1995, Van Pett et al, 2000) and primates (Sanchez et al, 2010). The opposing effects of CRF and UCN on serotonin were established in rodents.…”
Section: Crf-r2mentioning
confidence: 99%
“…By contrast, steroids increase serotonin effects in the brain by acting through the CRF system, which include decreased CRF transport to serotonin neurons and decreased CRFR1 expression, in conjunction with an increase in UCN1 transported caudally and an increase in CRFR2 and CRF-binding protein expression. As a result, the increase in serotonin action elevates mood, increases stress resistance, and decreases anxiety (32). Nevertheless, CRF-deficient mice display normal behavioral responses to stressors (33).…”
Section: Effects Of Crf Family Peptides On Anxiety-like Behavior Crfmentioning
confidence: 99%
“…All of these actions could translate to improved mood and stress resilience in women. In addition, we found that administration of E or E+P to ovariectomized macaques decreased CRF gene and protein expression in the PVN of macaques (Bethea and Centeno, 2008), decreased CRF innervation of the dorsal and median raphe, decreased CRF-R1 receptors and increased CRF-R2 receptors in the dorsal raphe, increased detectable midbrain urocortin (UCN1) cell number and increased UCN1 fiber densitiy (Sanchez et al, 2010). Together these data suggest that ovarian hormone administration may improve stress resilience through the serotonin, CRF and UCN systems.…”
Section: Introductionmentioning
confidence: 99%